Sarcoidosis with ankylosing spondylitis: changing therapeutic landscape - Rahul, Chinnabhathini Deva; Sharma, Rahul Kumar; Talwar, Deepak (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Sarcoidosis is an inflammatory multisystem disease which rarely may coexist in patients with other autoimmune disease like ankylosing spondylitis (AS). The presence of such as association causes diagnostic and management dilemmas as sarcoidosis has been reported to develop in patients of AS treated with tumour necrosis factor alpha (TNF-α) inhibitors. We describe a 49-year-old male with ankylosing spondylitis and histologically proven sarcoidosis who was treated with infliximab and improved.